Studies in Health Technology and Informatics Volume 27 - Towards Security in Medical Telematics - Barber, B. (IOS Press, 2014)
The issues presented at the workshop and this book are critical because telematics technology is now being used throughout the health care system for dealing with very sensitive data. More and more computers and systems are interconnected, they operate around the clock, they are increasingly interoperable, data are portable, and yet the primary demands are that they are correct, not corrupted, relevant, complete, and accessible only to authorised persons; data and systems must be secure. This raises technological and legal, regulatory, and ethical issues that are dealt within a national context, but also at the Community level in the form of proposals for EU directives on data protection and concerning the protection of personal data and privacy in the context of digital telecommunications networks. However, in most instances, the regulations are of a general nature and not specifically directed at health care.